Socialization of Automatic Distance Sensor Technology Implementation in Charity Boxes - Ashoumi, Hilyah; Hariono, Tholib; Al-Ghozali, M. Dzikrul Hakim; Wardani, Dian Kusuma (Talenta Publisher, 2023)
The purpose of this service activity is to apply the design of the mosque charity box tool with a good security system and improve skills and productivity in young men and women. The target of the implementation of Automatic Proximity Sensor Technology in the Charity Box in the Tembelang Village area, Tembelang District, Jombang Regency are young men and women. This activity was carried out at the AL-Hasan Balongombo TPQ Hall, Tembelang Village, Tembelang District, Jombang Regency with 20 participants. The implementation method uses PAR (Participatory Action Research) or so-called participatory action research, action research is related to an agenda for social change that embodies the belief in gathering knowledge to define problems to be solved. Then evaluate the activities using a Likert scale questionnaire form, with the results that 50% of the material presented is in accordance with the needs of partners and 60% of partners are satisfied with the implementation of this outreach activity.